2020
DOI: 10.15184/aqy.2020.49
|View full text |Cite
|
Sign up to set email alerts
|

A great wave: the Storegga tsunami and the end of Doggerland?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 58 publications
0
13
1
1
Order By: Relevance
“…The shallow palaeobathymetry of this newly submerged topography may have had a significant effect on the wave energy dispersion of the tsunami, concentrating it in some areas, and mitigating it in others. Contrary to earlier propositions, however, the tsunami would not have been the instigator of a permanent sea-level rise (Walker et al, 2020).…”
Section: The Southern North Sea Basincontrasting
confidence: 74%
See 2 more Smart Citations
“…The shallow palaeobathymetry of this newly submerged topography may have had a significant effect on the wave energy dispersion of the tsunami, concentrating it in some areas, and mitigating it in others. Contrary to earlier propositions, however, the tsunami would not have been the instigator of a permanent sea-level rise (Walker et al, 2020).…”
Section: The Southern North Sea Basincontrasting
confidence: 74%
“…However, a more nuanced understanding is beginning to emerge in the wake of numerical modelling of the wave's dispersal (Hill et al, 2014;Hill et al, 2017), and the discovery of the first confirmed evidence of the tsunami from a submarine context, "core ELF001A" from the "Southern River" submerged river valley, recovered by the Europe's Lost Frontiers team (Gaffney et al, 2020). Clearly the Storegga tsunami hit some of the coastlines of the southern North Sea with considerable force, but the severity of this impact was probably variable (Walker et al, 2020).…”
Section: The Southern North Sea Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the magnitude of the Storegga tsunami in the northern North Sea, as evidenced by sediment deposits and predicted by model simulations [4,6,7], there has been a surprising lack of physical evidence to suggest the tsunami reached the southern North Sea (Figure 1) [3,8]. Furthermore, whilst the same model suggests that if the tsunami did reach the southern North Sea the actual impact within this area has been the subject of debate [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, whilst the same model suggests that if the tsunami did reach the southern North Sea the actual impact within this area has been the subject of debate [8]. [8].…”
Section: Introductionmentioning
confidence: 99%